TRANSITIVE VERBS IN THE RUSSIAN LANGUAGE - Ahmedova Feruza Ibragimovna (International Scientific and Current Research Conferences, 2025)
This article explores the grammatical category of transitive verbs in the Russian language, emphasizing their case behavior, syntactic patterns, and pedagogical implications. Examples and teaching strategies are provided to help learners master usage, alongside a brief comparison with English transitivity.